Singularité du Bois Borassus Aéthiopum par sa physiologie - Komlan Lolo; Sonnou Tiem (European Scientific Journal, ESJ, 2017)
Among the traditional building materials in Togo, the Borassus Aéthiopum or Rônier is one of the most widely used. The singularity of this wood made it famous because of its resistance to xylophages and to the various inclement weather. But the determining factors of this resistance are unknown. This work aims to show the singularity of this wood under different observation angles. In this work, we study the physiology of this wood. We will observe samples taken at different locations under different scales. In view of the results obtained, we decide on the particularity of this wood. The rônier is made of detachable fibers.